2019
DOI: 10.1021/acs.molpharmaceut.9b00101
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)-block-poly(2-aminoethyl methacrylate hydrochloride)-Based Polyplexes as Serum-Tolerant Nanosystems for Enhanced Gene Delivery

Abstract: Incorporation of poly­(ethylene glycol) (PEG) into polyplexes has been used as a promising approach to enhance their stability and reduce unwanted interactions with biomolecules. However, this strategy generally has a negative influence on cellular uptake and, consequently, on transfection of target cells. In this work, we explore the effect of PEGylation on biological and physicochemical properties of poly­(2-aminoethyl methacrylate) (PAMA)-based polyplexes. For this purpose, different tailor-made PEG-b-PAMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…1,2 Although many cationic polymer carriers have been developed to realize efficient gene transfection, some defects, such as low solution stability, poor serum compatibility, high cytotoxicity and low cellular uptake, have still largely restricted their practical applications. 3 To overcome the defects, it was disclosed that conjugation/modication of cationic polymers on their backbones/side chains with biocompatible building blocks: polyethylene glycol (PEG), [4][5][6] carbohydrates, 7,8 zwitterionic molecules 9 and natural products, 10 was an efficient way to reduce cytotoxicity and improve bioavailability. Meanwhile, researchers made great efforts to elucidate the structure-function relationships of cationic polymers so as to obtain the optimal balance between gene transfection efficiency and cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although many cationic polymer carriers have been developed to realize efficient gene transfection, some defects, such as low solution stability, poor serum compatibility, high cytotoxicity and low cellular uptake, have still largely restricted their practical applications. 3 To overcome the defects, it was disclosed that conjugation/modication of cationic polymers on their backbones/side chains with biocompatible building blocks: polyethylene glycol (PEG), [4][5][6] carbohydrates, 7,8 zwitterionic molecules 9 and natural products, 10 was an efficient way to reduce cytotoxicity and improve bioavailability. Meanwhile, researchers made great efforts to elucidate the structure-function relationships of cationic polymers so as to obtain the optimal balance between gene transfection efficiency and cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to improve the capacity of polymeric nanoparticles to overcome the intracellular barriers and consequently increase the transfection efficacy, Santo et al constructed poly(2-aminoethyl methacrylate) (PAMA)-based polyplexes covered with PEG and evaluated the efficiency of in COS-7 and HepG2 cell lines. The results showed that the nanosystem covered with PEG increased the transfection activity and decreased the cytotoxicity [232]. Zhupanyn and co-workers evaluated the application of PEIs nanoparticles conjugated with extracellular vehicle (ECV) to deliver siRNA in different cell lines.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…immunizations (4 weeks apart) with a very low dose (1 microgram) of the plasmid PCV-tat delivered by these nanoparticles followed by one or two protein boosts induced significant antigen-specific humoral and cellular responses and greatly increased Th1-type T cell responses and CTLs against HIV-1 Tat [ 242 ]. Along similar lines, PEG was covalently bound to the cationic polymer poly (2-aminoethyl methacrylate hydrochloride) in order to improve the stability of nanstructures in vivo [ 243 ]. Figure 13 shows the core–shell microparticles obtained by Castaldello and coworkers, 2006, incorporating both functionalities, cationic charge and the stability, in aqueous medium imparted by PEG [ 242 ].…”
Section: Hybrid Cationic Assemblies Of Biocompatible Polymer/catiomentioning
confidence: 99%